Circumvention of Immunity to the Adenovirus Major Coat Protein Hexon - Roy, Soumitra (American Society for Microbiology, 1998)
Immunity to adenoviruses is an important hurdle to be overcome for successful gene therapy. The presence of antibodies to the capsid proteins prevents efficacious adenovirus vector administration in vivo. We tested whether immunity to a particular serotype of adenovirus (Ad5) may be overcome with a vector that encodes the hexon sequences from a different adenovirus serotype (Ad12). We successfully constructed an adenovirus vector with a chimeric Ad5-Ad12 hexon which was not neutralized by plasma from C57BL/6 mice immunized with Ad5. The vector was also capable of transducing the livers of C57BL/6 mice previously immunized with Ad5.